Study the effect of Enterobacter cloacae on the gene expression, productivity, and quality traits of Curcuma longa L. Plant - Alrajeh, Hind Salih; Sherif, Fadia El (Frontiers in Plant Science, 2024)
Overuse of artificial chemical fertilizers could be detrimental to the environment. Utilizing beneficial microorganisms as biofertilizers is a sustainable technique that promotes soil health, crop yield, and ecosystem preservation. Curcuma longa L. is utilized as a medication since it has its antibacterial, anti-microbial, and anti-tumor characteristics, which reduce inflammation and hasten wound healing. Therefore, the aim of this research is to explore how Enterobacter cloacae affects the production and chemical contents (photosynthetic pigment, nitrogen, phosphorus, potassium, and curcuminoid) of Curcuma longa L. grown under greenhouse conditions. Our research showed that Curcuma longa's growth and yield were favorably impacted by Enterobacter cloacae. Significant increases in the related plants' chlorophyll a,b, carotenoid, nitrogen, phosphorus, and potassium levels were likewise a reflection of the enhanced effects shown in the growth and yield parameters. Treatment with Enterobacter cloacae raised the curcuminoid's three sub-components' compositions to varying degrees: bisdemethoxycurcumin, demethoxycurcumin, and curcumin. Comparing Enterobacter cloacae treated plants to the control, high expression levels of the genes diketide-CoA and curcumin synthase-1, -2, and 3 were also found. The treatment of Enterobacter cloacae is a good biostimulant candidate for boosting growth and yield as well as raising the medicinal qualities of Curcuma longa, according to the overall results.